Analysis of crystal structure and reflection loss of material based on La0.7Sr0.3Mn1-x(Ni, Ti)x/2O3 (x=0.1, 0.3, and 0.5) applications for microwave absorbers - Sitti Ahmiatri Saptari; Nada Hashida Lathifah; Arif Tjahjono; Deni Shidqi Khaerudini (Journal of Physics: Theories and Applications, 2022)
In this research, structural engineering of lanthanum manganite material based on La0.7Sr0.3Mn1-x(Ni,Ti)x/2O3 (x = 0.1; 0.3 and 0.5) was synthesized using the sol-gel method. The prepared samples were then characterized using X-ray Diffraction (XRD) and Vector Network Analyzer (VNA). X-Ray Diffraction (XRD) characterization results obtained a single. Substitution of Ni and Ti ions with a concentration of x = 0.1; 0.3; and 0.5 indicate that the formed sample has a rhombohedral structure with a space group R -3c, the presence of Ni and Ti ion substitution does not cause a change in the structure but there is a change in the lattice parameters and crystal size. Vector Network Analyzer (VNA) characterization in the range of 8 – 12 GHz produces the most optimal reflection loss intensity value of -11.8 dB at an optimal frequency of 10.58 GHz at a concentration of x = 0.5 with the ability to absorb microwaves of 93.39%. Thus the material La0.7Sr0.3Mn1-x(Ni,Ti)x/2O3 (x = 0.1; 0.3 and 0.5) can be used as a microwave absorbent material.